Treatment of severe dry eye following acoustic neuroma surgery with eyelid androgen gel application - Jay Ruzhang Jiang; Rima Khankan; William H. Ridder, III; Jerry R. Paugh (American Journal of Ophthalmology Case Reports, 2025)
Purpose: To report a case of recalcitrant dry eye disease caused by acoustic neuroma and subsequent microsurgery. Observations: A 51-year-old female presented with refractory unilateral (right eye) severe dry eye disease (DED). The patient had a history of right acoustic neuroma with surgical excision 14 years prior. With normal eyelid closure, the patient reported persistent dry eye symptoms despite use of several tear substitutes and ointments. The patient was a subject in a clinical trial, and was found to be in the active treatment arm following unmasking. The patient had been dosed with a topical eyelid application of testosterone 4.5 % wt./wt. gel twice per day for 4 weeks and followed up to 8 weeks after discontinued drug application. Dry eye symptoms were significantly improved and brought to near normal range (Ocular Surface Disease Index (OSDI) < 13). Tear break up time, meibomian secretion quality, and tear osmolarity were also improved to near normal levels in both the affected and unaffected eyes. In the affected eye, ocular surface staining and Schirmer result were improved from baseline at week 12, but remained below normal values. Conclusions and importance: The recalcitrant DED secondary to an acoustic neuroma and subsequent microsurgery resection was due to injury of the nervus intermedius, resulting in aqueous deficient DED. Topical testosterone treatment on the eyelids ameliorated the DED by improving symptoms and restoring some clinical signs to near-normal levels, suggesting that this may potentially be a new treatment approach in aqueous deficient dry eye.